HYPNOBIRTHING AS A THERAPEUTIC COMMUNICATION METHOD IN MOTHER AND CHILD HOSPITAL ANNISA PEKANBARU - Annisa Salsabila; Yustikasari (Media Inovasi Pendidikan dan Publikasi, 2023)
This research was conducted to find out why hypnobirthing is used as a therapeutic communication method, to find out how hypnobirthing is applied, and to find out the therapeutic communication model of RSIA Annisa. Using a qualitative method with a case study approach. Data collection techniques are through in-depth interviews, observation, literature study, and documentation. Data analysis techniques using flow model analysis. The results of the study, RSIA Annisa uses hypnobirthing as a therapeutic communication method to help pregnant women to manage stress, fear and anxiety during pregnancy so as to facilitate the delivery process. Starting from a concern for the welfare of mothers and children, RSIA Annisa builds personal relationships that result in psychologically fostered relationships in accordance with their motto